Diaquabis(ethylenediamine-κ2N,N′)copper(II) bis(4-phenylbenzoate) 2.66-hydrate - José A. Fernandes; Ana I. Ramos; Patrícia Silva; Susana S. Braga; Paulo Ribeiro-Claro; João Rocha; Filipe A. Almeida Paz (Acta Crystallographica Section E, 2010)
In the title complex, [Cu(C2H8N2)2(H2O)2](C13H9O2)2·2.66H2O, the CuII centre (located at an inversion centre) is coordinated by two bidentate ethylenediamine (en) ligands and two water O atoms in a typical Jahn–Teller distorted octahedral geometry. The amino groups and the water molecules are disordered over two distinct crystallographic positions with occupancies of 1/3 and 2/3. In the crystal, the cations and anions are disposed in alternating layers. One of the water molecules of crystallization is disordered and the other has a fractional occupation. In the 2/3 occupancy component, water molecules are organized into a chain composed of hexameric units interconnected by carboxylate bridges.